Anxious Vigilance and the Production of (Il)legitimacy in the UK Citizenship Regime: "It's How You Sift Them Out, Y'know?". Issue 1 (1st June 2022) - Lewis, Rachel
Abstract: This article examines the navigation and enactment of vigilance in the UK citizenship regime. Drawing on data from a four-year research project in a UK city, including observations of citizenship ceremonies and interviews with institutional actors and citizen-candidates, it sees vigilance as a central feature of the naturalization process, with watchfulness oriented toward three key areas: the bureaucratic precision, the linguistic proficiency, and the commitment to the nation evidenced by the citizen-candidate. It sees the navigation of anxious vigilance among all actors—state, institutional, and citizen-candidates—but argues that this is directed unevenly, with the state's securitizing gaze particularly maintained upon those racialized as Other. Reading citizenship in domopolitical terms as a technology through which the securitized state can enact its bordering practices, it sees the vigilance enacted in the naturalization process as productive: as working to realize the legitimacy of the state and the Good citizen, to articulate and exclude from membership those deemed illegitimate, and, ultimately, to curtail possibilities for solidarity.